2019
DOI: 10.1016/j.heliyon.2019.e02808
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-based bone tissue engineering for veterinary practice

Abstract: Bone tissue engineering has been widely studied and proposed as a promising platform for correcting the bone defects. The applications of mesenchymal stem cell (MSC)-based bone tissue engineering have been investigated in various in vitro and in vivo models. In this regard, the promising animal bone defect models have been employed for illustrating the bone regenerative capacity of MSC-based bone tissue engineering. However, most studies aimed for clinical applications in human. These evidences suggest a knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…We found that the potential cMSC resources for canine BTE were cBM-MSCs and cDPSCs, due to their plasticity, availability, and accessibility 4 , 21 . From our preliminary study and published report, cMSCs behaved differently from human MSCs (hMSCs) regarding the osteogenic differentiation potential (in-house data) 8 , 9 . We found that cMSCs showed matrix mineralization earlier than hMSCs did, so the osteogenic differentiation process and underlying mechanism might be different between cMSCs and hMSCs.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We found that the potential cMSC resources for canine BTE were cBM-MSCs and cDPSCs, due to their plasticity, availability, and accessibility 4 , 21 . From our preliminary study and published report, cMSCs behaved differently from human MSCs (hMSCs) regarding the osteogenic differentiation potential (in-house data) 8 , 9 . We found that cMSCs showed matrix mineralization earlier than hMSCs did, so the osteogenic differentiation process and underlying mechanism might be different between cMSCs and hMSCs.…”
Section: Discussionmentioning
confidence: 98%
“…According to the correction of skeletal and maxillofacial bone defects in veterinary practice, trend of stem cell-based regenerative treatment is of interest, especially for the application of BTE 9 . In this regard, the potential stem cell resources for the generation of bone-forming cells are the crucial factors determining the success of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations